Brazilian Amnesty Commission: Policies of Reparation and Truth and Memory - Fernando Goya Maldonado (Sortuz, 2015)
This article intends to expose the policies of reparation and truth and memory promoted by the Brazilian Amnesty Commission and one of it projects. Regarding this, it will reflect on Brazilian military dictatorship through a transitional justice perspective. However, the paper’s aim does not have as principal focus evaluated those policies; instead plans to expose the debate, looking for the policy justifications and principal critiques. Therefore, it does not aspire to promote one point of view, pro or against the policies, but prefers to discuss the mechanisms of public politics that are associated with them. This investigation will be done by – first – by contextualization, in order to understand the context and actors related to the Brazilian Military Dictatorship, then, by the transitional justice theory and the policies of Amnesty Commission. Lastly, it will sum the points of conclusion.